IMPLEMENTASI MODEL PEMBELAJARAN JIGSAW UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PADA MATA KULIAH IPS SD/MI DI PRODI PGMI IAIN FATTAHUL MULUK PAPUA - Nur’im Septi Lestari (WANIAMBEY : Jurnal Pendidikan Dasar Islam, 2020)
Jigsaw Learning Model is a type of cooperative learning that consists of several members who are responsible for mastering the learning material section and can teach the material to other members in the group. This research was conducted to increase student motivation and learning outcomes by implementing the Jigsaw Learning Model in social studies subjects at an elementary school. The approach used in this study is qualitative research, while the research method is qualitative classroom action research (CAR). The location of this research is the PGMI study program of IAIN Fattahul Muluk Papua and the data collection techniques such as observation, documentation study test, and interview. The data analysis technique uses a comparative approach. The results of this research, there was an increase in motivation and learning outcomes of the PGMI Study Program in IAIN Fattahul Muluk Papua from observation data in cycle I and cycle II. In the first cycle, the student learning motivation was 70.25%, and in the second cycle, the student motivation increased to 77.25%, there is an increase of 7.25%. While the enhancement in learning achievement is, in the pre-test the average score of students was 62.50, then in the first cycle the average value 9 students were 77.50, and in the second cycle test, the average value of students was 79.50 , there is an enhancement compared to the previous test.